Glutamate reduces glucose utilization while concomitantly enhancing AQP9 and MCT2 expression in cultured rat hippocampal neurons - Tescarollo, Fabio; Covolan, Luciene; Pellerin, Luc (Frontiers in Neuroscience, 2014)
The excitatory neurotransmitter glutamate has been reported to have a major impact on brain energy metabolism. Using primary cultures of rat hippocampal neurons, we observed that glutamate reduces glucose utilization in this cell type, suggesting alteration in mitochondrial oxidative metabolism. The aquaglyceroporin AQP9 and the monocarboxylate transporter MCT2, two transporters for oxidative energy substrates, appear to be present in mitochondria of these neurons. Moreover, they not only co-localize but they interact with each other as they were found to co-immunoprecipitate from hippocampal neuron homogenates. Exposure of cultured hippocampal neurons to glutamate 100 µM for 1 hour led to enhanced expression of both AQP9 and MCT2 at the protein level without any significant change at the mRNA level. In parallel, a similar increase in the protein expression of LDHA was evidenced without an effect on the mRNA level. These data suggest that glutamate exerts an influence on neuronal energy metabolism likely through a regulation of the expression of some key mitochondrial proteins.